An exploratory study on perceived online learning experience of university students during the COVID-19 pandemic - Singh, Priyanka; P. J., Shyju; Ranjan, Ranjeeva; Dubey, Binayak Kumar; Singh, Chandra Shamsher Bahadur (Institute of Advanced Engineering and Science, 2024)
The COVID-19 pandemic accelerated the pace of online learning amidst the health crisis unprecedentedly. Students worldwide witnessed the transition of the education system from physical classes to virtual mode and adapted themselves to accommodate the challenges and sustain the learning process. This study was carried out to understand the emotional factors and student engagement in various activities during the pandemic and to examine the perceived learning experience. The present study explored the perceived experience of university students in online learning in India. The study used a survey method and data was collected using a structured questionnaire. Results showed that students adapted to online education in the later phase better than the initial stage. The study reported increased stress levels among students. A two-way group analysis of selected variables (gender, age, stress, and loneliness) on perceived learning issues demonstrated significant results. The study’s findings revealed students’ experiences in online learning practice and develop the scope for further discussions to improve the learning process in online settings.